'Satisficing' system of systems using dynamic and static doctrines. (3rd December 2009) - Gorod, Alex; DiMario, Michael; Sauser, Brian; Boardman, John
System of systems (SoS) is a concept used to describe capabilities resulting from the network-centric connectivity of systems whereby the elements of a system are classified as summative or constitutive. The summative system owes its capabilities to the summation of the characteristics and sub-capabilities of its elements. The constitutive system has capabilities greater than the summation of its elements. The constitutive system concept demonstrates a potential need to shift the traditional systems engineering focus to address the problems of multiple integrated complex systems for which a final solution is not necessarily the end expectation. The objective involves 'satisficing' a holistic system. By examining the auto battle management aid (ABMA) case study, we conclude that dynamic and static doctrines provide us with an opportunity to observe a newly developed management framework. The goal includes creating a framework that would allow us to effectively 'satisfice' the management demands of an ever-changing SoS environment.